Influence of High School Students’ Science Subject Preferences on Their Science Identities, Motivation in Science, and Values of Science - Aghekyan, Rosa (International Journal of Educational Studies, 2025)
This study aimed to investigate the impact of high school students’ science subject preferences on their science learning, including science identities, motivation, and values of science. The participants included 3,454 high school students ranging from 9th to 12th grade, attending urban, suburban, and private schools across three different states. Quantitative data was collected through a survey instrument called SIEVEA and employed various statistical methods, such as descriptive analysis, predictive analysis (including one-way and two-way ANOVA), as well as correlation and Chi-square tests, to analyze the gathered data. The findings of this study revealed that students' science subject preferences play a significant role in shaping their science identities and the value they place on science. Moreover, notable differences were observed between urban and suburban students in terms of their science subject preferences. Although this research offers valuable insights into the variations in students' science subject preferences based on school type (urban versus suburban), further investigation is recommended. This additional research will aid in the development of enhanced curricula, identification of suitable resources, increased student engagement, and informed policy decisions.